2003
DOI: 10.1016/j.curtheres.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the clinical use of albumin: comparison of use in two Italian hospitals and a third hospital without guidelines

Abstract: Background: In the absence of clinical practice guidelines prior to 1999, the consumption of human albumin in the Liguria region of Italy was very high, despite possible adverse effects, limited supply, and significant cost.Objective: The purpose of this study was to assess the impact of comprehensive guidelines on the amount of albumin used in 2 general hospitals and to compare it with that of a third general hospital that did not adopt the guidelines.Methods: We analyzed the influence of the guidelines on al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…On the other hand, this could be attributed to the lack of a defined guidelines for albumin infusion in the neonatal period. Martelli et al found that the adoption of guidelines may substantially reduce the inappropriate use of albumin [16]. In our study albumin infusion resulted in increased serum albumin levels in all of the cohort, which goes in line with a result by two major clinical trials SAFE [17] and ALBIOS [18] both documented a small but statistically significant increase in serum albumin level following albumin administration.…”
Section: Association Of Liver and Kidney Function Tests Before And After Treatment With Patients' Outcomesupporting
confidence: 90%
“…On the other hand, this could be attributed to the lack of a defined guidelines for albumin infusion in the neonatal period. Martelli et al found that the adoption of guidelines may substantially reduce the inappropriate use of albumin [16]. In our study albumin infusion resulted in increased serum albumin levels in all of the cohort, which goes in line with a result by two major clinical trials SAFE [17] and ALBIOS [18] both documented a small but statistically significant increase in serum albumin level following albumin administration.…”
Section: Association Of Liver and Kidney Function Tests Before And After Treatment With Patients' Outcomesupporting
confidence: 90%
“…This decrease resulted in a cost savings of €17 000 for the first hospital and €200 000 for the second hospital. 17 A study of SICU patients at a tertiary teaching hospital found that the introduction of albumin restriction criteria resulted in a 54% decrease in albumin use, 56% reduction in cost, and had no negative impact on ICU length of stay or mortality. 3 Finally, a recently published study evaluating the impact of restriction criteria for albumin prescribing in a single-center cardiac surgery ICU found that the introduction of restriction criteria reduced utilization of albumin by 64% and resulted in a monthly cost savings of $45 000.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the purpose of our study, several previous studies have evaluated the effectiveness of various interventions conducted by hospital transfusion management systems to promote appropriate use of blood products. Studies conducted in 1 hospital in Iran [22], 1 hospital in Italy [23], and 2 hospitals in Italy [24] reported that the implementation of hospital guidelines on the clinical use of HA performed by some kinds of hospital transfusion management system could reduce HA consumption by 36%, 15–20%, and 7.6–77.4%, respectively. Other studies conducted in 1 hospital in India [21] and 1 hospital in Portugal [25] reported that an educational intervention conducted by the hospital transfusion management system may be an effective measure to promote appropriate clinical use of blood products.…”
Section: Discussionmentioning
confidence: 99%